Association between sleep disturbances and suicidal behavior in adolescents: a systematic review and meta-analysis - Baldini, Valentina; Gnazzo, Martina; Rapelli, Giada; Marchi, Mattia; Pingani, Luca; Ferrari, Silvia; De Ronchi, Diana; Varallo, Giorgia; Starace, Fabrizio; Franceschini, Christian; Musetti, Alessandro; Poletti, Michele; et al. (Frontiers in Psychiatry, 2024)
Introduction: Adolescents' health and well-being are seriously threatened by suicidal behaviors, which have become a severe social issue worldwide. Suicide is one of the leading causes of mortality for adolescents in low and middle-income countries, with approximately 67,000 teenagers committing suicide yearly. Although an association between sleep disturbances (SDs) and suicidal behaviors has been suggested, data are still scattered and inconclusive. Therefore, to further investigate this association, we conducted a meta-analysis to verify if there is a link between SDs and suicidal behaviors in adolescents without diagnosed psychiatric disorders.Methods: PubMed, CENTRAL, EMBASE, and PsycINFO were searched from inception to August 30th, 2024. We included studies reporting the estimation of suicidal behaviors in adolescents from 12 to 21 years of age, with SDs and healthy controls. The meta-analysis was based on odds ratio (OR, with a 95% confidence interval ([CI]), estimates through inverse variance models with random-effects.Results: The final selection consisted of 19 eligible studies from 9 countries, corresponding to 628,525 adolescents with SDs and 567,746 controls. We found that adolescents with SDs are more likely to attempt suicide (OR: 3.10; [95% CI: 2.43; 3.95]) and experience suicidal ideation (OR: 2.28; [95% CI 1.76; 2.94]) than controls.Conclusion: This meta-analysis suggests that SDs are an important risk factor for suicidal ideation and suicide attempts in healthy adolescents. The findings highlight the importance of early identification of SDs to prevent suicidal behaviors in this population.